1974
DOI: 10.1073/pnas.71.10.4229
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol as a Bioregulator in the Development and Inhibition of Leukemia

Abstract: Leukemia in mice and humans is accompanied by a marked deficiency of unesterified cholesterol in the surface membrane of leukemic cells as compared to normal leukocytes. This deficiency induces a significant reduction in their membrane microviscosity. Since cholesterol in the cell surface membrane is exchangeable with cholesterol in the serum lipoproteins, concomitant to the cellular deficiency of cholesterol, the average level of cholesterol in the blood serum of leukemic patients is substantially below the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(29 citation statements)
references
References 29 publications
(22 reference statements)
2
27
0
Order By: Relevance
“…High membrane fluidity in CLL lymphocytes due to low membrane cholesterol levels, which are reflected in reduced serum cholesterol concentrations, have been reported by a number of groups. [63][64][65] In addition, leukaemic leukocytes display substantial increases in sterol synthesis compared with cells isolated from healthy controls. 66,67 Malignant transformation of lymphocytes to highly proliferative CLL cells surely involves major usage and reorganisation of critical membrane components, such as cholesterol, a molecule transported from the liver through the blood stream primarily in VLDL and LDL.…”
Section: Classification Methodsmentioning
confidence: 99%
“…High membrane fluidity in CLL lymphocytes due to low membrane cholesterol levels, which are reflected in reduced serum cholesterol concentrations, have been reported by a number of groups. [63][64][65] In addition, leukaemic leukocytes display substantial increases in sterol synthesis compared with cells isolated from healthy controls. 66,67 Malignant transformation of lymphocytes to highly proliferative CLL cells surely involves major usage and reorganisation of critical membrane components, such as cholesterol, a molecule transported from the liver through the blood stream primarily in VLDL and LDL.…”
Section: Classification Methodsmentioning
confidence: 99%
“…Using this technique it was reported that the "microviscosity" of mouse lymphoma cells and liposomes prepared from them is markedly lower than that of normal mouse lymphocytes and the corresponding liposomes . The same authors have also reported that the "microviscosity" of isolated surface membranes from human chronic lymphocytic leukaemia (CLL) cells was also considerably less than that of normal human lymphocytes (Inbar and Shinitzky, 1974b). These differences in apparent "microviscosity" appear to reflect mainly the lower cholesterol/phospholipid ratio in the leukaemic and lymphoma cell when compared with normal lymphocytes (Shinitzky and Inbar, 1976 …”
mentioning
confidence: 97%
“…Free cholesterol incorporated into the cytoplasmic membrane suppresses membrane fluidity (13,24) and nuclear DNA synthesis (1,12). As reported in a previous paper cholesterol oleate is also incorporated into the cell membrane, but much faster than is free cholesterol, and it has similar biological activities (19).…”
mentioning
confidence: 58%